Expansion of the small cable television counterparts of market leading commercial channels in view of Hungarian regional and social aspects - Illés, Gabriella (Acta Agraria Debreceniensis, 2014)
Currently, there are 102 Hungarian-language television channels in Hungary. TV2 Hungary is the second largest commercial television channel. Current trends in the television market in Europe indicate that large channels are expanding their portfolios while at the same time selling their smaller units. This trend has now affected Hungary as well. After having TV2 for 16 years, MTM-SBS Television Ltd. eventually expanded its portfolio with three new cable channels. The first new channel was FEM3, a channel directed at women, which was launched on January 1, 2010. A year later, the male channel, PRO4, was launched and finally, SuperTV2, primarily a premium entertainment channel, was launched on November 2, 2012. Although the main channel, TV2, remained free, the new pay channels on cable received a significant amount of investment from venture capitalists and Pro7Sat1 for the development of new content. SuperTV2 is a premium channel. When the channel was launched, the goal was to target those viewers who had turned away from watching the increasingly less-sophisticated content on the commercial channels as well as those who were not drawn to the programming on public television. When the viewer stats were examined, the channel had proven itself. The premium brand of Super TV2 was successful in attracting new viewers and consumers and within a year it had gained a strong foothold over more than 100 other Hungarian-language channels.